The Routledge Handbook of Language Program Development and Administration - Cox, Troy | https://orcid.org/0000-0001-9379-5102; Brown, Alan | https://orcid.org/0000-0003-0144-4722; Malone, Margaret | https://orcid.org/0000-0001-9640-412X (Taylor & Francis, 2026)
Second language program development and administration is a long-standing area within the larger field of applied linguistics. In many ways, it is the quintessential applied linguistics field, as it crosses disciplinary boundaries while balancing the rigors of scholarly inquiry with the demands of practical application without losing sight of concrete learner outcomes. The Routledge Handbook of Language Program Development and Administration provides a scholarly rigorous, yet practically relevant treatment of issues implicated in program development and administration with 52 chapters written by leading scholars in the field. Authors not only address the theoretical underpinnings of their respective topics but also provide actionable, evidence-based recommendations concerning eminently practical matters. In this way, the volume provides both novice and experienced language program administrators with important guidance on how to think about the work that they do and how best to go about it, while also validating language program administration as a scholarly area of inquiry. The Routledge Handbook of Language Program Development and Administration is essential reading for practicing second language program administrators at the post-secondary level, in-service and pre-service second language instructors, graduate students in applied linguistics, and even upper-level undergraduate education students considering second language teaching as a future career. Chapters 9 and 11 of this book are freely available as downloadable Open Access PDFs at http://www.taylorfrancis.com under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 license.